2022
DOI: 10.1093/europace/euac215
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile and long-term efficacy of very high-power short-duration (60–70 W) catheter ablation for atrial fibrillation: results of a large comparative analysis

Abstract: Aims This retrospective study sought to compare complication rates and efficacy of power-controlled very high-power short-duration (vHPSD) and conventional catheter ablation in a large cohort of patients with atrial fibrillation (AF). Methods and results We analyzed 1115 consecutive patients with AF (38.7% paroxysmal, 61.3% persistent) who received first-time catheter ablation at our centre from 2015 to 2021. Circumferential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The most used CF‐sensing catheters for AF ablation today include SmartTouch or SmartTouch SF (Biosense Webster, Irvine, USA) and TactiCath catheter (Abbott, Illinois, USA). Previous large, randomized trials for treatment of AF using these catheters showed 100% successful acute PV isolation and treatment efficacy range of 66.4%–72.5% 6–9 . In the present study, the acute successful PVI isolation and rate of freedom from AF and other atrial arrhythmias at one year reached 100% and approximately 81%, respectively.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The most used CF‐sensing catheters for AF ablation today include SmartTouch or SmartTouch SF (Biosense Webster, Irvine, USA) and TactiCath catheter (Abbott, Illinois, USA). Previous large, randomized trials for treatment of AF using these catheters showed 100% successful acute PV isolation and treatment efficacy range of 66.4%–72.5% 6–9 . In the present study, the acute successful PVI isolation and rate of freedom from AF and other atrial arrhythmias at one year reached 100% and approximately 81%, respectively.…”
Section: Discussionsupporting
confidence: 53%
“…Previous large, randomized trials for treatment of AF using these catheters showed 100% successful acute PV isolation and treatment efficacy range of 66.4%-72.5%. [6][7][8][9] In the present study, the acute successful PVI isolation and rate of freedom from AF and other atrial arrhythmias at one year reached 100% and approximately 81%, respectively. The high effectiveness of the novel catheter is due to technological advances and may also be related to improved ablation strategies in recent years.…”
Section: Ablation Effectivenesssupporting
confidence: 47%
“… 20 Recently, also very high-power short-duration (vHPSD) ablations with 60–70 W were found to be comparably safe and even more efficient than ablations with conventional power. 21 …”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] HPSD is associated with a similar safety profile and with equivalent to improved long-term rhythm outcomes as standard RFA, while consistently reducing procedural duration. [7][8][9][10] PFA is a novel, nonthermal cardiac ablation modality using highvoltage electric fields to create nanoscale pores in the cell membrane through a mechanism known as irreversible electroporation. 11,12 Cell membrane disruption compromises cell homeostasis eventually leading to cell death.…”
Section: Introductionmentioning
confidence: 99%